2021
DOI: 10.3390/ijerph18136876
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Good-Quality Antenatal Care and Birthing Services among Postpartum Women in Nepal

Abstract: Patient complaints and dissatisfaction should be taken seriously and used as an opportunity to provide acceptable services. Mounting evidence shows that the perception of the quality of healthcare services impacts health-seeking behaviors. This study explores the perceptions of good-quality antenatal and birthing services among postpartum women. A qualitative study using phenomenological inquiry was conducted in the Morang district, Nepal. The study participants were postpartum women with at least one high-ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 50 publications
(72 reference statements)
0
8
0
Order By: Relevance
“…A plausible mechanism underlying this association is that women with a higher number of ANC visits have a higher awareness of pregnancy-related complications. Thus, they are more likely to seek professional delivery care services [ 28 , 29 ]. So, the women who have more ANC visits at a health facility have more chances to meet skilled birth personnel and thus to have delivery there by them.…”
Section: Discussionmentioning
confidence: 99%
“…A plausible mechanism underlying this association is that women with a higher number of ANC visits have a higher awareness of pregnancy-related complications. Thus, they are more likely to seek professional delivery care services [ 28 , 29 ]. So, the women who have more ANC visits at a health facility have more chances to meet skilled birth personnel and thus to have delivery there by them.…”
Section: Discussionmentioning
confidence: 99%
“…Girls usually left school before or shortly after marriage, negatively affecting their knowledge of reproductive and maternal health which was often taught in school [ 45 , 46 , 48 , 49 , 51 , 54 56 , 58 , 60 , 69 , 80 , 100 , 109 , 113 , 115 ]. This 17-year-old mother expressed how her lack of education negatively affected pregnancy preparedness:…”
Section: Resultsmentioning
confidence: 99%
“…Related to this, pregnant women and girls generally felt embarrassed and ashamed when discussing their pregnancy [ 17 , 44 , 72 , 83 , 89 , 91 , 99 , 104 , 115 ]. Women who were younger, less educated, and had a faster transition from childhood to pregnancy tended to be more shy and embarrassed when discussing their pregnancy [ 44 , 46 , 62 , 72 , 83 , 91 , 99 , 120 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with those from wealthier households, women from poorer households often have more limited health knowledge and less access to essential health services, including PNC. 23 , 28 , 29 In addition, attendance of four or more ANC visits was found to be strongly associated with higher quality of maternal and neonatal PNC, as there is an increased opportunity for mothers to become more informed about potential complications and receive greater encouragement to seek high-quality PNC. 30 Moreover, our study found that advanced maternal age was associated with quality PNC, which was consistent with the findings of studies conducted in Nepal and Uganda.…”
Section: Discussionmentioning
confidence: 99%